The Effect of the Whole Group Discussion Learning Method on Students’ Learning Interest - Syarifuddin, Ahmad; Fajriansyah, Kautsar; Faisal, Faisal; Padli, Padli (PAI RAFAH, 2025)
This study examines how to increase the learning interest of seventh-grade students in studying Islamic Jurisprudence (Fiqih) using the Whole Group Discussion learning method, which shows that this method is effective in increasing students’ learning interest. This study uses a quantitative approach with a one group pretest posttest design to determine the differences in students’ learning interest before and after the implementation of the Whole Group Discussion method, which includes several stages, such as planning, implementation, and evaluation. The results of this study show that there is a significant difference between student’s learning interest at the pretest, with the results of the t-test hypothesis using paired sample test obtaining a significant value of 0.02 < 0.05. Based on the testing rules, if the sig. (2-tailed) value is < 0.05, then Ho is rejected and Ha is accepted, so it can be concluded that there is a significant influence of the Whole Group Discussion learning method on students' learning interest in Fiqih subject for seventh-grade students. Thus, this study provides empirical evidence that the implementation of the Whole Group Discussion method can increase students’ learning interest in studying Fiqih, so this method can be used as an alternative to improve the quality of learning in schools. Based on the results of the research conducted by the researcher, it can be concluded that there is a significant influence of the Whole Group Discussion learning method on students' learning interest in Fiqih subjects for seventh-grade students, so teachers can consider this method in the learning procces to increase students, interest and engagement.